2019
DOI: 10.1111/tpj.14162
|View full text |Cite|
|
Sign up to set email alerts
|

The genome of the medicinal plant Andrographis paniculata provides insight into the biosynthesis of the bioactive diterpenoid neoandrographolide

Abstract: These authors contributed equally to this work. ‡ These authors are corresponding co-authors. SUMMARYAndrographis paniculata is a herbaceous dicot plant widely used for its anti-inflammatory and anti-viral properties across its distribution in China, India and other Southeast Asian countries. A. paniculata was used as a crucial therapeutic treatment during the influenza epidemic of 1919 in India, and is still used for the treatment of infectious disease in China. A. paniculata produces large quantities of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 109 publications
(114 reference statements)
5
69
2
Order By: Relevance
“…The phylogenetic distribution of putative and functionally characterized UGTs has thus far been analyzed in a total of 27 plant genera with fully sequenced genomes, including one chlorophycean algae ( Chlamydomonas reinhardtii ), one bryophyte ( Physcomitrella patens ), one lycophyte ( Selaginella moellendorffii ) and 24 angiosperms (Li et al ., ; Yonekura‐Sakakibara and Hanada, ; Barvkar et al ., ; Caputi et al ., ; Schweiger et al ., ; Li et al ., ; Huang et al ., ; Wu et al ., ; Xu et al ., ; Yu et al ., ; He et al ., ; Rehman et al ., ; Cheng et al ., ; Song et al ., ; Sun et al ., ; Figure ; Table ). In the two analyses with the largest datasets, 12 and 16 genera were examined, respectively, and identified groups O and P UGTs that are absent in A. thaliana (Yonekura‐Sakakibara and Hanada, ; Caputi et al ., ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The phylogenetic distribution of putative and functionally characterized UGTs has thus far been analyzed in a total of 27 plant genera with fully sequenced genomes, including one chlorophycean algae ( Chlamydomonas reinhardtii ), one bryophyte ( Physcomitrella patens ), one lycophyte ( Selaginella moellendorffii ) and 24 angiosperms (Li et al ., ; Yonekura‐Sakakibara and Hanada, ; Barvkar et al ., ; Caputi et al ., ; Schweiger et al ., ; Li et al ., ; Huang et al ., ; Wu et al ., ; Xu et al ., ; Yu et al ., ; He et al ., ; Rehman et al ., ; Cheng et al ., ; Song et al ., ; Sun et al ., ; Figure ; Table ). In the two analyses with the largest datasets, 12 and 16 genera were examined, respectively, and identified groups O and P UGTs that are absent in A. thaliana (Yonekura‐Sakakibara and Hanada, ; Caputi et al ., ).…”
Section: Introductionmentioning
confidence: 96%
“…A characteristic and relatively conserved 44‐amino acid plant secondary product glycosyltransferase (PSPG) motif has been found at the C‐terminus of plant UGTs, which interacts with the sugar donor. In the model plant Arabidopsis thaliana , 123 UGTs have been identified, which belong to 21 gene families, and are organized into 14 phylogenetic groups (A–N) and an outgroup (OG; Ross et al ., ; Stucky et al ., ; He et al ., ; Sun et al ., ; http://www.p450.kvl.dk/At_ugts/table.shtml). The well‐supported OG is formed by UGTs that modify sterols and lipids; these enzymes are divergent from the other plant UGTs and the PSPG motif is less conserved (Paquette et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The protective role may be due to the direct reaction of compounds of Andrographis with free radicals 42,44 and showed remarkable retrieval in body and organ weights, regulate the enzymic and non-enzymic antioxidant defenses and other metabolic indices along with a reduction in arsenic levels of ovary 45 . Studies by Kishore et al, 46,47 also reported that AP inhibits the formation of oxygen-derived free radicals and normalized the level of antioxidant indices 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Andrographis paniculata known as 'Chuan-Xin-Lian' in Chinese, which is well known and historically documented in both traditional Chinese medicine (TCM) in China (Pholphana et al 2013). Andrographis paniculata can be used to treat a variety of diseases as the traditional Chinese medicine in China, such as diarrhea, fevers, laryngitis, gastric infections and upper respiratory tract infections (Sun et al 2019). So, to enhance the development of its medicinal value, we reported and characterized the complete chloroplast genome sequence of A. paniculata in an effort to provide genomic resources useful to promoting its medicinal value and systematic research.…”
mentioning
confidence: 99%